ANALISIS PENERAPAN DISIPLIN KERJA PADA CV. SINAR INDAH MEDAN - WENY .; CAROLINE NATALIA; JOSI FARMIATI; ELSERRA SIEMIN CIAMAS; TASIK UTAMA (JURNAL ILMIAH MAKSITEK, 2019)
This research aims to determine the application of employee discipline in CV. Sinar Indah Medan. The subject in this study issecretary, finance manager, operational manager, supervisor, accounting, Operational adm, cashier. The theory used isaccording to Singodimedjo (Sutrisno, 2013), a discipline that is the attitude and willingness of a person to understand andadhere to the prevailing regulatory norms surrounding it. In other words, discipline is an attitude of obedience or obedience tothe rules of the prevailing rules in an organization. The research method used in this research is a qualitatively descriptivemethod, the method of collecting data is interviews. The sampling technique used is purposive sampling. The methods ofdata analysis used are methods of analysis of Miles and Huberman. The validity of the data used is source tringulation. Theresults of the study said that the work discipline of employees at CV. Sinar Indah Medan is lacking. Some things to be awareof are the attitude of employee discipline to the company and sanctions given by the company to its employees.